Injection 3D concrete printing in a carrier liquid - Underlying physics and applications to lightweight space frame structures. (November 2021) - Lowke, Dirk; Vandenberg, Aileen; Pierre, Alexandre; Thomas, Amaury; Kloft, Harald; Hack, Norman
Abstract: Currently, additive manufacturing in concrete construction can be divided into three main methods: firstly, material extrusion, secondly material spraying, and thirdly particle bed binding, with the material typically being applied in layers. In contrast, Injection 3D Concrete Printing (I3DCP) is based on the concept that a fluid material A is deposited spatially free into a material B with specific rheological properties, keeping material A in a stable position within material B. Thus, in contrast to the layered deposition of horizontal strands, free-form three-dimensional concrete structures can be printed entirely in one piece. In general, three versions of Injection 3D Concrete Printing can be classified: a) injecting a fine-grained concrete into a non-hardening carrier liquid; b) injecting a non-hardening suspension into a fine-grained concrete; c) injecting fine-grained concrete with specific properties into concrete with different properties. This paper focuses on Injection 3D Concrete Printing into a carrier liquid. For a deeper understanding of the underlying physical mechanisms, we carry out experiments that vary the rheological properties of the carrier liquid, the concrete flow rate, and the nozzle displacement velocity. We use a ground limestone suspension as carrier liquids in this study. We investigate the effect of the rheological properties of the carrier liquid on the positional stability of the injected concrete in small-scale print experiments. Based on this, we develop an analytical model that describes the positional stability as a function of the rheological properties. Also, we highlight that the final cross-section of the injected concrete strand is dependent on the concrete flow rate and nozzle velocity. Finally, we present the first reinforced I3DCP-elements and current developments of this novel technology for lightweight space frame structures in concrete construction.